ADSORPTION BEHAVIOUR OF CITRIC ACID FROM AQUEOUS SOLUTIONS ON ACTI VATED CHARCOAL - Khan, A Rasteed; Uddin H, Faltim; Ahmed, S Zaka (Biological Sciences - PJSIR, 2002)
Adsorption of cit ric acid at d i fferent concentration s on acti vated charcoal at 22° has been acconp l_i shed. I t as fou nd that at low concentrations, langm u i r and Freund lich equations arc wel l obeyed. The adsorption oJ citric acid irom aqu eous solution on the surface of charcoal is mono layer.